2022
DOI: 10.1186/s12880-022-00838-x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Computed Tomography examinations in Uganda: Towards determining the National Diagnostic Reference Levels

Abstract: Introduction Diagnostic Reference Levels (DRLs), typically set at the 75th percentile of the dose distribution from surveys conducted across a broad user base using a specified dose-measurement protocol, are recommended for radiological examinations. There is a need to develop and implement DRLs as a standardisation and optimisation tool for the radiological protection of patients at Computed Tomography (CT) facilities. Methods This was a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Ultrasonic imaging is radiation free, simple to operate, provides real-time results, and is low cost [ 20 ]. CT imaging is fast and widely used to diagnose diseases of the skeletal system, chest, abdomen [ 21 , 22 ], etc. The imaging process of MRI is radiation free and non-invasive to the human body, and the imaging effect on soft tissues, bone marrow, joints, and other parts is better than CT [ 23 , 24 ].…”
Section: Overview Of Medical Imaging Technologymentioning
confidence: 99%
“…Ultrasonic imaging is radiation free, simple to operate, provides real-time results, and is low cost [ 20 ]. CT imaging is fast and widely used to diagnose diseases of the skeletal system, chest, abdomen [ 21 , 22 ], etc. The imaging process of MRI is radiation free and non-invasive to the human body, and the imaging effect on soft tissues, bone marrow, joints, and other parts is better than CT [ 23 , 24 ].…”
Section: Overview Of Medical Imaging Technologymentioning
confidence: 99%
“…Yurt et al(2020) suggests that technical capacity of radiologists in public and private hospitals also account for variations in mean CTDIvol and DLPs. Technical capacity determines how providers or clinical staff chose to set the machine technical parameters which affect dose levels 10,28 Abba and Ibrahim (2018) reported higher values of CTDIvol and DLPs in public health facilities as opposed to private health facilities. Similarly, Erem et al, (2022) found out that public health facilities had higher mean values for CTDIvol and DLPs when compared to private health facilities.…”
Section: B Comparison Of the Ctdi(w) And Dlp Values For Adult Abdomin...mentioning
confidence: 99%
“…Technical capacity determines how providers or clinical staff chose to set the machine technical parameters which affect dose levels 10,28 Abba and Ibrahim (2018) reported higher values of CTDIvol and DLPs in public health facilities as opposed to private health facilities. Similarly, Erem et al, (2022) found out that public health facilities had higher mean values for CTDIvol and DLPs when compared to private health facilities. The authors explained that in public health facilities there is the likelihood of having an aging machine or poorly maintained scanner that may yield values outside the accepted standards for effective radiation dose optimization.…”
Section: B Comparison Of the Ctdi(w) And Dlp Values For Adult Abdomin...mentioning
confidence: 99%